Solve the system by graphing

1) x + y = 3

x + y = -1

2) 3x + y = 6

3x - y = 0

Printable View

- Apr 6th 2007, 12:08 PMPatiencegraphing equalities
Solve the system by graphing

1) x + y = 3

x + y = -1

2) 3x + y = 6

3x - y = 0 - Apr 6th 2007, 12:26 PMearboth
Hello, Patience,

to 1)

The graphs of both equations are straight lines. Since the two lines are parallel there isn't any intersection and therefore there exists noch solution,

to 2)

I've attached the graphs. The solution of this system of linear equations consists of the coordinates of the intersection: A(1, 3) means x = 1 and y = 3

EB